2004
DOI: 10.1007/s00125-004-1521-5
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profile and insulin antibody IgG subclasses in patients with recent onset Type 1 diabetes treated with oral insulin

Abstract: Aims/hypothesis. Tolerance to orally administered antigens may be generated through the induction of T helper cell type 2 and 3 (Th2/Th3) regulatory cells. We previously reported that treatment of recent onset Type 1 diabetes with oral insulin had no effect on residual beta cell function. The aim of this study was to evaluate whether this treatment produces a deviation in the immune response, with polarisation of the cytokine pattern and the induction of a Th2-like antibody response. Methods. Mononuclear cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Mucosal tolerance has been proposed as a means to induce Ag-specific protection in inflammatory diseases, ranging from autoimmune disease to transplant rejection and allergy (3,4). However, successful translation of prevention of disease in animal models to therapeutic application in human disease proved to be difficult (5)(6)(7)(8)(9)(10)(11). The disappointing outcome of clinical trials can be explained by several facts, such as: the trials were performed in end-stages of disease; the patient populations studied were inherently diverse; and there was a lack of pretreatment screening to determine whether the Ag was immunologically relevant in patients to be treated.…”
mentioning
confidence: 99%
“…Mucosal tolerance has been proposed as a means to induce Ag-specific protection in inflammatory diseases, ranging from autoimmune disease to transplant rejection and allergy (3,4). However, successful translation of prevention of disease in animal models to therapeutic application in human disease proved to be difficult (5)(6)(7)(8)(9)(10)(11). The disappointing outcome of clinical trials can be explained by several facts, such as: the trials were performed in end-stages of disease; the patient populations studied were inherently diverse; and there was a lack of pretreatment screening to determine whether the Ag was immunologically relevant in patients to be treated.…”
mentioning
confidence: 99%
“…Intranasal insulin has been given to islet autoantibody-positive subjects as young as 2 years of age without side effects [28,29]. Immunologic studies suggested some modulation of immune response to insulin in these studies [28,43]. The INIT I (Intranasal Insulin Trial) in particular showed that administration of intranasal insulin was associated with an overall increase in antibodies and a decrease in T-cell responses to insulin [28], similar to that seen in the mouse model.…”
Section: Why Mucosal Administration Of Insulin?mentioning
confidence: 84%
“…Two studies in patients with new-onset T1DM administering insulin orally at doses ranging from 2.5 to 7.5 mg/d (together with standard insulin replacement therapy) could not demonstrate obvious benefit in preserving residual -cell function [26,27]. However, one of these studies demonstrated increases in the regulatory cytokine TGF- [43]. In a cohort of 372 prediabetic islet cell antibody-and IAApositive relatives of T1DM patients aged 3 to 45 years, no significant beneficial effects were achieved by administering oral insulin, 7.5 mg/d [9•].…”
Section: Why Intervene Early In the Disease Development?mentioning
confidence: 96%
“…Hayashi et al (1998) also suggested that IFN-γ might play a role in islet inflammation leading to islet cell destruction. Monetini et al (2004) informed that the release of IFN-γ was markedly reduced in patients treated with oral insulin.…”
Section: Discussionmentioning
confidence: 99%